1997
DOI: 10.1007/s001250050712
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitogen-activated protein kinase expression and activity in white adipose tissue of ventromedial hypothalamus-lesioned rats

Abstract: In rats made obese by electrolytic lesion of the ventromedial hypothalamus (VMH), the onset of the syndrome is determined by the time of the lesion, allowing a chronological study of the alterations associated with obesity. Lesion of the VMH induces hyperphagia, hyperinsulinaemia and obesity [1], associated with alterations in the cellularity and metabolism of the white adipose tissue (WAT). After the lesion, there is an initial period of rapid weight gain (dynamic phase) followed by a slowing in the rate of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…LRRK2 has been shown to affect signal transduction pathways, including the ERK module, and may in uence autophagy (Carballo-Carbajal et al 2010). Interestingly, the ERK pathway is known to be upregulated in adipose tissue in response to certain stimuli, including diet-induced obesity (Combettes-Souverain et al 1997). Lastly, Feng et al (2011) investigated whether adipocyte cell death is a consequence of macrophage in ammation, or vice versa, in the context of a high-fat diet, and suggested that a adipocyte cell death is an intrinsic response independent of macrophage in ltration, which may explain the upregulation of PDCD10 in INGWAT.…”
Section: Discussionmentioning
confidence: 99%
“…LRRK2 has been shown to affect signal transduction pathways, including the ERK module, and may in uence autophagy (Carballo-Carbajal et al 2010). Interestingly, the ERK pathway is known to be upregulated in adipose tissue in response to certain stimuli, including diet-induced obesity (Combettes-Souverain et al 1997). Lastly, Feng et al (2011) investigated whether adipocyte cell death is a consequence of macrophage in ammation, or vice versa, in the context of a high-fat diet, and suggested that a adipocyte cell death is an intrinsic response independent of macrophage in ltration, which may explain the upregulation of PDCD10 in INGWAT.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were anaesthetized intraperitoneally with 95 mg ketamineakg body weight (Imalgene 500, Bio-Me Ârieux, France) and VMH lesions were carried out as described previously. 14,15 For the determination of blood glucose, plasma insulin and plasma lipids, a catheter was implanted into the carotid artery as previously described.…”
Section: Animalsmentioning
confidence: 99%